Elastic pseudo xanthoma. A case presentation. - María Dolores Castillo Menéndez; Julián V. Viera Yániz; Eunice Díaz de Villegas; Manuel Sabatés Martínez; Roxana Novoa Encinas (Medisur)
There is a case of a 42 years old patient that went to the doctor because she has been suffering from cutaneous lesions and her situation was worsening with time. The lesions presented themselves in form of ¨orange peel¨, with yellow papules that caused plates on the neck, armpits, and other body creases, without associated simptoms. We concluded, by clinic diagnosis, corroborated by histiopathology, that we were dealing with an elastic pseudosantoma.